Gestational Diabetes Mellitus Upregulates Vitamin D Receptor in Extravillous Trophoblasts and Fetoplacental Endothelial Cells. (March 2015) - Knabl, Julia; Hüttenbrenner, Rebecca; Hutter, Stefan; Günthner-Biller, Maria; Riedel, Christina; Hiden, Ursula; Kainer, Franz; Desoye, Gernot; Jeschke, Udo
Objective: Gestational diabetes mellitus (GDM) is often accompanied by low maternal vitamin D, that is, calcitriol (1, 25[OH]2 vitamin D3), levels. Here, we tested the hypothesis that the placental vitamin D receptor (VDR) is regulated by calcitriol and altered in GDM with distinct changes in different placental cell types. Specifically, we aimed to localize VDR in human term placentas from normal and GDM pregnancies, to quantify its cellular expression and to study in vitro its regulation by its physiological agonist calcitriol. Study Design: Placental tissue slides of 80 patients (40 with GDM/40 controls) were double stained for VDR and human leukocyte antigen G to identify extravillous trophoblasts (EVTs). Staining intensity was semiquantified. Quantitative real time-polymerase chain reaction and Western blotting measured VDR messenger RNA (mRNA) and protein in decidual tissue. The trophoblast cell line BeWo was used to study in vitro VDR regulation by calcitriol (0.01, 0.1, and 1 nmol/mL). Results: Vitamin D receptor protein and mRNA levels are upregulated ( P < .05) in EVT (1.8-fold) as well as in placental endothelium (5.8-fold) of patients with GDM. Expression of VDR is regulated by calcitriol in a bimodal manner: high doses (0.1 and 1 nmol/mL) caused downregulation, whereas the low dose (0.01 nmol/mL) resulted in VDR upregulation. Conclusion: Vitamin D receptor is upregulated in EVT and endothelium of GDM placentas. This could be due to low maternal vitamin D levels in patients with GDM because in vitro low calcitriol doses upregulate VDR in trophoblast cells.